PENGARUH LIABILITAS DAN EKUITAS TERHADAP PROFITABILITAS (STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021) - Ninda Kusuma Wulandari; Ali Riza Fahlevi; Cantika Adelia; Dewi Kusmayanti; Nike Sekariesta (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This study aims to examine the effect of liabilities and equity on profitability (Studies of Banking Companies Listed on the Indonesia Stock Exchange in 2019-2021). The samples and data in this study were taken from banking companies listed on the IDX for 2019-2021 in the financial statements and annual reports for that period. The method used is sampling. The method used in this study uses the normality test method with multiple linear regression analysis. Based on the research results, liability has a positive and significant effect on profitability, while equity has no effect and is not significant on profitability.